Path Analysis on the Biopsychosocial Factors Affecting the Quality of Life in Patients with Breast Cancer - Dewi, Rizka Amalia; Mudigdo, Ambar; Pamungkasari, Eti Poncorini (Journal of Epidemiology and Public Health, 2020)
Background: Breast cancer is the most com